Land value creation and benefit distribution in the process of rural-urban land conversion: A case study in Wuhan City, China. (March 2021) - Xie, Xiangxiang; Dries, Liesbeth; Heijman, Wim; Zhang, Anlu
Abstract: With the rapid development of urbanization, industrialization and decentralized fiscal reform in China, large areas of farmlands are being converted from rural land to urban construction (residential, commercial and industrial) land. Taking Wuhan City in Hubei Province, China as a case study, we analyze land value creation by value creators including farmers (collectives), the government and developers at the level of the individual parcel, community, township and district in the process of rural-urban land conversion from farmland to residential, commercial and industrial use. The results show that (1) at the individual analysis level, land prices increase significantly during the process of land acquisition, land leasing and real estate development and sales. Land prices and incremental values differ greatly across the three land types, with higher prices for residential and commercial land, and lower prices for industrial land. In addition, farmers (collectives) receive the lowest share of the land value revenue, while the highest share is obtained by developers, followed by the government. (2) At the community, township and district levels of analysis, the spatial distribution of land values shows similar characteristics at different scales. Moreover, scale effects are found in land value creation and benefit distribution. Average land prices and incremental values decrease from the scale of the community, to the township, to the district. Furthermore, the difference in land values decreases gradually when moving from the community scale to the district scale. This study contributes to a better understanding of land value increments and benefit distribution at multiple levels of analysis, for multiple stakeholders, and for multiple land use types. Highlights: Land prices increase significantly during the process of land acquisition, leasing and real estate development and sales. Scale effects are found in land value creation and benefit distribution. Urban land developers share the highest benefit, follow by the government and farmers.